Submit Manuscript Browse Journal Info Guide for Authors Article Processing Charges (APC) Reviewers Call for Reviewers Contact Us Strength and durability enhancement of self compacting concrete using multi walled carbon cano tubes and cano titanium dioxide: A comparative analysis - Barodawala, Qasimali Ibrahim; Mishra, Sushree Sangita (Al-Qadisiyah journal for engineering science, 2025)
Multi-walled carbon nanotubes (MWCNTs) have been widely used, especially in concrete applications. Further studies reveal that nano titanium dioxide (TiO₂) is also used in concrete to intensify the properties of concrete. This study investigates the effects of adding various percentages (0.1%, 0.3%, and 0.5%) of MWCNTs and nano TiO₂ to M40 grade self-compacting concrete. The mechanical properties—compressive, split tensile, and flexural strength—along with durability aspects such as water absorption, rapid chloride penetration, and acid resistance were evaluated. The findings indicate that with addition of 0.1%, 0.3% & 0.5% Multi-walled carbon nanotubes (MWCNTs) 2%,8% and 21% average increment respectively in compressive strength is observed after 28 days, whereas other tested parameters are also showing significant increment. Similarly, with addition of 0.1%, 0.3% & 0.5% of nano titanium dioxide (TiO₂) 5%,6% and 10% average increment respectively in compressive strength was observed after 28 days. The durability parameters are also enhanced for both the nano materials but MWCNTs shows more increment when compared to nano TiO2.The cost comparison of both the nano materials is also taken into consideration which shows that around 14 lakhs of material cost required for 0.1 % MWCNT is more when compared to 0.1% nano TiO2 required for casting 100m3 of self-compacting concrete.